2016
DOI: 10.1080/14719037.2016.1192160
|View full text |Cite
|
Sign up to set email alerts
|

Ventures in public value management: introduction to the symposium

Abstract: This essay reviews the development of public value management, tracing its rise from relative obscurity in the 1990s to the global attention it receives today. We also introduce the accompanying essays in this symposium which aim to spur further development in the years to come. We review the main tenets of public value management and highlight the key debates in the literature, discussing the mandate of public managers visa -vis politicians, the mobilization of 'the public', the framing of strategic challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 46 publications
0
57
0
2
Order By: Relevance
“…First foreshadowed by Allison (1986) (see also (Heymann 1987)), developed and conceived largely by Moore (1995Moore ( , 2013 it is now being taken up by increasing numbers of practitioners and scholars (O'Flynn 2007;Alford and O'Flynn 2009;Benington and Moore 2011;Bryson et al 2014Bryson et al , 2015Talbot 2009;Alford et al 2017;Mulgan 2008;Barzelay and Campbell 2003;Llewellyn and Tappin 2003;Poister 2010;Meier et al 2007;Weinberg and Leeman 2013). This framework acknowledges both the public and "business" imperatives that government organizations face.…”
Section: The Public Value Frameworkmentioning
confidence: 99%
“…First foreshadowed by Allison (1986) (see also (Heymann 1987)), developed and conceived largely by Moore (1995Moore ( , 2013 it is now being taken up by increasing numbers of practitioners and scholars (O'Flynn 2007;Alford and O'Flynn 2009;Benington and Moore 2011;Bryson et al 2014Bryson et al , 2015Talbot 2009;Alford et al 2017;Mulgan 2008;Barzelay and Campbell 2003;Llewellyn and Tappin 2003;Poister 2010;Meier et al 2007;Weinberg and Leeman 2013). This framework acknowledges both the public and "business" imperatives that government organizations face.…”
Section: The Public Value Frameworkmentioning
confidence: 99%
“…Alford et al () recognize that in Moore's account building legitimizing constituencies is a necessary part of strategic public management and can include ‘lawmakers, interest groups, regulators, clients and … the general public’. Creating the authorizing environment means building a public demand for action.…”
Section: Discussionmentioning
confidence: 99%
“…The article adopts a multi‐theoretical approach to the research questions identified. It makes use of Alford and Head's recent () assessments of ‘wicked problems’. Were the article to focus on domain‐specific policy challenges, for example in respect of social media, Kingdon's multiple streams analysis and Sabatier's advocacy coalition framework might have been utilized to examine developments.…”
Section: Data Methods Theorymentioning
confidence: 99%
“…The operating capacity is therefore essential to the actual creation of public value. As Alford et al (, p. 591) note, ‘it is no good articulating a public value proposition and getting support for its execution if the public manager [or metagovernor] cannot muster the organizational capacity required to deliver on it’. So metagovernors need to ‘manage down’ within their own organizations to align resources, people and processes to the task.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The concept of public value has gained momentum in scholarly and managerial debates (Alford et al ). It describes the value that an organization or network contributes to society.…”
Section: Introductionmentioning
confidence: 99%